Ex Vivo, In Vitro and In Vivo Bone Health Properties of Grana Padano Cheese - Cristina Martelli; Luisa Ottobrini; Anita Ferraretto; Paola Bendinelli; Stefano Cattaneo; Fabio Masotti; Milda Stuknytė; Margherita Dall’Asta; Angelo Del Sole; Ivano De Noni; Filippo Rossi (Foods)
Grana Padano (GP) is an Italian hard cooked cheese characterized by a long ripening process and high protein and Ca contents. After in vitro static simulated gastrointestinal digestion, GP digest contained caseinophosphopeptides that were 6 to 24 amino acids in length, including tri-phosphorylated species incorporating the pSer-pSer-pSer-Glu-Glu cluster. Using rat ileum tissue, the digest was used to assess Ca absorption ex vivo, which showed significantly better results for the GP digest in comparison to the CaCO3 aqueous solution. An in vitro intestinal model based on Caco-2/HT-29 cell co-culture was able to mimic Ca absorption from GP digest, with Ca-rich water as a control. The metabolite-containing medium was then used to treat osteoblast-like SaOS-2 cells. As a consequence, metabolized GP digest significantly increased the number of osteoblasts, whereas the metabolized water did not exert this effect. Finally, the mice were fed diets containing GP or CaCO3 and pea isolate and the in vivo outcomes were assessed through fluorescent probe and computed tomography. Mice fed a diet containing GP showed a higher increase in bone remodeling and volume in comparison to those fed a control diet containing CaCO3 and pea isolate. Overall, the ex vivo, in vitro and in vivo experiments highlighted the effectiveness of GP in improving Ca absorption, osteoblast proliferation and bone remodeling and volume.